An integrated model to select an ERP system for Chinese small- and medium-sized enterprise under uncertainty - Zeng, Yu-Rong; Wang, Lin; Xu, Xian-Hao (Technological and Economic Development of Economy, 2017)
Enterprise Resource Planning (ERP) system is a vital investment that can significantly affect future competitiveness and performance of small- and medium-sized enterprises (SMEs). Selecting the best desirable ERP software covering both qualitative and quantitative factors has been the most critical problem for a long time. On the other hand, multiple criteria decision making has been found to be a useful approach to analyze conflicting factors. Qualitative criteria are often accompanied by ambiguities and vagueness. This makes fuzzy and grey logic become more natural approaches to handle this kind of problem. This paper presents a new approach for the selection of SME-specific ERP systems. Firstly, criteria for SMEs in China to evaluate the most suitable ERP system are put forward using group-discussing and anonymous questionnaire methods. An effective and practical algorithm, which is integrated of modified Delphi, analytic hierarchy process, fuzzy comprehensive evaluation and grey relational analysis, is utilized to convert the qualitative description to quantitative data to select the most appropriate alternative in the presence of vagueness and uncertainty. Finally, the potential use of the proposed model is illustrated through a case study. First published online: 02 Nov 2015